2014
DOI: 10.1039/c3sc52326h
|View full text |Cite
|
Sign up to set email alerts
|

Germanium(iii) corrole complex: reactivity and mechanistic studies of visible-light promoted N–H bond activations

Abstract: Germanium(III) corrole complex: reactivity and mechanistic studies of visible-light promoted N-H bond activationsFang, H.; Ling, Z.; Lang, K.; Brothers, P.J.; de Bruin, B.; Fu, X.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 40 publications
(17 reference statements)
2
51
0
Order By: Relevance
“…Coordination-induced bond weakening, whereby interaction of a ligand results in a considerable lowering of the X-H BDFE, has recently been identified or implicated in rare instances (18)(19)(20)(21)(22)(23) and has been applied by Knowles's group (24) and others (25)(26)(27) in reactions of organic molecules involving N-H and O-H bonds, respectively. Cuerva's group (26,27) and ours (28) have demonstrated the effectiveness of bis(cyclopentadienyl) titanium(III) complexes in weakening the O-H bonds of water and the N-H bonds of ammonia.…”
mentioning
confidence: 99%
“…Coordination-induced bond weakening, whereby interaction of a ligand results in a considerable lowering of the X-H BDFE, has recently been identified or implicated in rare instances (18)(19)(20)(21)(22)(23) and has been applied by Knowles's group (24) and others (25)(26)(27) in reactions of organic molecules involving N-H and O-H bonds, respectively. Cuerva's group (26,27) and ours (28) have demonstrated the effectiveness of bis(cyclopentadienyl) titanium(III) complexes in weakening the O-H bonds of water and the N-H bonds of ammonia.…”
mentioning
confidence: 99%
“…Exploiting the concept of bond-weakening upon coordination to redox-active metals [223][224][225][226][227][228][229][230][231][232], our lab demonstrated that a redox-active titanium catalyst Cp* 2 Ti III Cl and a weak hydrogen atom acceptor TEMPO enable intramolecular additions of amides to Michael acceptors ( Figure 32) [223]. The substrate scope allows for N-H activation of amides, carbamates, thiolcarbamates, and ureas bearing phenyl or electron-rich arenes in uniformly high yield.…”
Section: Amidesmentioning
confidence: 99%
“…40 (Figure 1b), distinct from most of the previously reported penta-coordinated germanium corrole complexes that exhibited a domed structure with the germanium atom significantly displaced from the N 4 plane. 36,43,44 This is ascribed to the more symmetric hexacoordination geometry and smaller radius of the cationic However, silicon and the heavier group 14 element cations are rarely observed to undergo this type of reaction. 6,37,45,46 Interestingly, the oily [(TPFC)Ge] + cation was observed to react with benzene quantitatively to form a new compound as brownish-black crystals at room temperature in a few days.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…The Xray crystal structure of (TPFC)Ge−C 6 H 5 (Figure 2b) showed a domed geometry similar to that of other penta-coordinated germanium corroles. 36 54 whereas the Si−C arene (distances ranging from 2.089 to2.231 Å) bond orders in previously reported silylium-arene adducts were calculated to be only from 0.20 to 0.35 (the D(1) value of 1.817 Å used here was as reported for the Si−C Mes bond length in [Mes 3 Si] + , 5 Mes = 2,4,6-trimethylphenyl). 6,37,46,55,56 This result also indicates that [(TPFC)Ge(η 1 -C 6 H 6 )] + is best described as a σ-type germylium-benzene adduct rather than a π-type complex.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation